More than meets the eye: Expanding and reviewing the clinical and mutational spectrum of brittle cornea syndrome. Issue 6 (6th April 2021) - Dhooge, Tibbe; Van Damme, Tim; Syx, Delfien; Mosquera, Laura M.; Nampoothiri, Sheela; Radhakrishnan, Anil; Simsek‐Kiper, Pelin O.; Utine, Gülen E.; Bonduelle, Maryse; Migeotte, Isabelle; Essawi, Osama; Ceylaner, Serdar; et al.
Abstract: Brittle cornea syndrome (BCS) is a rare autosomal recessive disorder characterized by corneal thinning and fragility, leading to corneal rupture, the main hallmark of this disorder. Non‐ocular symptoms include not only hearing loss but also signs of connective tissue fragility, placing it in the Ehlers‐Danlos syndrome (EDS) spectrum. It is caused by biallelic pathogenic variants in ZNF469 or PRDM5, which presumably encode transcription factors for extracellular matrix components. We report the clinical and molecular features of nine novel BCS families, four of which harbor variants in ZNF469 and five in PRDM5 . We also performed a genotype‐ and phenotype‐oriented literature overview of all ( n = 85) reported patients with ZNF469 ( n = 53) and PRDM5 ( n = 32) variants. Musculoskeletal findings may be the main reason for referral and often raise suspicion of another heritable connective tissue disorder, such as kyphoscoliotic EDS, osteogenesis imperfecta, or Marfan syndrome, especially when a corneal rupture has not yet occurred. Our findings highlight the multisystemic nature of BCS and validate its inclusion in the EDS classification. Importantly, gene panels for heritable connective tissue disorders should include ZNF469 and PRDM5 to allow for timely diagnosis and appropriate preventive measures for this rare condition. Abstract : Brittle cornea syndrome is a rare autosomal recessive disorder characterized by corneal fragility, in addition to signs of connective tissue fragility. The genotype‐ and phenotype‐oriented overview of the newly identified patients (n = 13) and previously reported patients (n = 72) with ZNF469 (n = 53) and PRDM5 (n = 32) variants highlights the multisystemic nature of the disease and its overlap with other heritable connective tissue disorders, such as kyphoscoliotic Ehlers‐Danlos syndrome, osteogenesis imperfecta, or Marfan syndrome.